Gonadal maturation, fecundity and hatching performance of wild caught tiger shrimp Penaeus monodon using unilateral eyestalk ablation in captivity - Uddin, SA; Rahman, MM (Journal of the Bangladesh Agricultural University, 2016)
In this study, the effects of eyestalk ablation on maturation, moulting, spawning and hatching rate of wild caught Penaeus monodon were investigated. Twenty males (M) and 30 eyestalkablated and 30 nonablated females (F), all individually marked (M: F=1:3) were stocked into two 15ton capacity (each) maturation tank. All the ablated females moulted in 7.92±0.24 (mean±standard error) days, and first spawning occurred 3.2±0.20 days following eyestalk ablation. While twenty-five ablated females spawned, producing an average of 296,160±26,589 eggs, only eight nonablated females spawned, producing an average of 195,462±20,565 eggs during the investigation period of 120 days. A significant positive correlation between fecundity and female body weight (P<0.05; P<0.001) was observed. Throughout the experiment, the average number of spawning per female was 1.8±0.14 for ablated and one for nonablated females. Multiple spawning (up to three times) occurred within the same moulting cycle in ablated females. Among the ablated P. monodon females, 36% spawn once, 48% second time, and 16% third time. The average fertility rate of the eggs was high, ranging between 80 and 90% in non-ablated females, while in ablated females; the range was between 72 and 88% and differ significantly (p<0.05) ablated and non ablated females. Average hatching rate ranges between 70 and 80% for ablated and 75 and 82% for non-ablated females (p<0.05). From eggs to nauplii production per female was 167,838 for ablated and 127,500for nonablated females. This study indicates that eyestalk ablation and environmental condition were important inducing tools for re-maturation of spent P. monodon that continued supply of seed stock for effective commercial shrimp farming. J. Bangladesh Agril. Univ. 13(2): 315-322, December 2015